Restoration of the name Lilium cupreum and its conservation significance - Shi, Pei-Ling; Wang, Ting; Xu, Ze-Bing; Herbert, Melvyn; Chen, Xiao-Juan; Wang, Jing-Bo; Yuan, Meng; Zhang, Zuo-Dong; He, Lei; Gao, Yun-Dong (Phytotaxa, 2026)
In this study, the previously overlooked name Lilium cupreum has been restored through field verification, morphological comparison and molecular phylogenetic analysis. The findings confirm the independent status of this species and clarify its taxonomic position in the lophophora clade in the genus Lilium of south-western China, providing a broader context for its classification. Field investigations and specimen surveys reveal that this species has a limited distribution and small populations, making it vulnerable to threats from human activities.